Chemotherapy-induced nausea and vomiting (CINV) with carboplatin plus pemetrexed or carboplatin plus paclitaxel in patients with lung cancer: a propensity score-matched analysis - Toshinobu Hayashi (BMC Cancer, 2021)
Abstract Background Patients with lung cancer who are treated with carboplatin-based chemotherapy regimens often experience chemotherapy-induced nausea and vomiting (CINV). However, knowledge on the effect of regimen and cofactors on the risk of CINV is limited. This study aimed to analyze and compare the incidence of CINV between lung cancer patients undergoing carboplatin plus pemetrexed (CBDCA+PEM) and those undergoing carboplatin plus paclitaxel (CBDCA+PTX) chemotherapy. Methods Pooled data of 240 patients from two prospective observational studies were compared using propensity score matching. Separate multivariate logistic regression analyses were used to identify risk factors for nausea and vomiting following chemotherapy. Results Delayed nausea was significantly more common in patients treated with CBDCA+PEM than in those treated with CBDCA+PTX (51.1% vs. 36.2%, P = 0.04), but the incidence of vomiting did not significantly differ between the two groups (23.4% vs. 14.9%, P = 0.14). The occurrence of CINV peaked on day 4 in the CBDCA+PTX group and on day 5 in the CBDCA+PEM group. Multivariate analysis showed that female sex, younger age, and CBDCA+PEM regimen were independent risk factors for delayed nausea, while female sex was an independent risk factor for delayed vomiting. Conclusions The CBDCA + PEM regimen has a higher risk of causing delayed nausea than the CBDCA + PTX regimen, and aggressive antiemetic prophylaxis should be offered to patients treated with CBDCA + PEM.